GAMBARAN EKSPRESI PADA PUISI AKU KARYA CHAIRIL ANWAR DENGAN MENGGUNAKAN KAJIAN EKSPRESIF - Ahmad Ilzamul Hikam; Muhammad Faisol (Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was conducted with the aim of knowing the value of the author's creativity in a literary work of poetry entitled Aku, by Chairil Anwar. The data source for this research is the content of the poem Aku, by Chairil Anwar. The research method used is descriptive qualitative method. This method is used on the basis of consideration and suitability of research forms and research objectives. While the data collection techniques in this study used documentation study techniques and data observation. The results of this research can be concluded that Charil Anwar, in creating his poem entitled Aku, tries to describe deep emotional expressions, such as loneliness and anxiety. This poem also reflects the rebellion against social conditions and the author's perceived oppression. Chairil Anwar uses imagery and symbolism to express feelings of limitations and the desire for individual freedom